Heuristic column generation for railroad track inspection scheduling - Lannez, Sébastien; Artigues, Christian; Damay, Jean; Gendreau, Michel (HAL CCSD, 2010)
International audience The problem we are solving is to visit a given set of tracks given that tracks can't be inspected all over the year and track outages can alter vehicles speed. Furthermore, vehicles speed depend on their type and circulation mode (either inspecting or not). These vehicles have limited capacity defined by the amount of water which can be brought on board. For organisational purposes, water tanks can only be refilled at the end of a shift and the objective is to minimise the total deadhead distance. We named this problem the Railroad Track Inspection Problem (RTISP).